Contributions to the history of bioethics: Comments to the work of James A. Drane - Perales Cabrera, Alberto (2001)
The excellent work of Dr. Drane required by the importance of the subject, beyond a review of contributions to complement their efforts. Try modestly to add some line of thought. Wisely, James A Drane, warns in his work: "how difficult it is to say exactly the beginning of any historical period or even the cultural development of an academic discipline 'In optics such judgment."To talk about the beginning of bioethics inevitably leads to speculation"